Solid state fermentation method for production of laccase enzyme with bagasse, cornstalk and rice husk as substrates for adrenaline biosensor - Meka Saima Perdani; Grace Margaretha; Muhamad Sahlan; Heri Hermansyah (Energy Reports, 2020)
Adrenaline is an important neurotransmitter in the body that will be released from the body when someone is in emotional state or in state of physical and emotional stress, such as hypoglycemia, work out, and excessive pain in the body. Early diagnosis based on the determination of adrenaline concentration in plasma and urine can prevent unnecessary drug use (Hollenbach et al., 1998 [1]). In adrenaline, there is an enzyme, called laccase. Laccase has wide application in industry and medical application. Moreover, the producing of laccase is need to be more develop to produce high activity of enzyme. The high activity enzyme will be affected to the determination of adrenaline concentration. Therefore, the aim of this research is to extract extracellular laccase from fermentation of Trametes versicolor with solid state fermentation method on lignocellulosic waste in the form of bagasse, corn stalk and rice husk. A utilization of biomass waste had applied in this work. We investigated the best pre-treatment condition to produce laccase. Steam explosion is used for the treatment of raw substrates. The best substrate for producing laccase was cornstalk with additional treatment of steam explosion and nutrient addition. Finally, investigation of substrates selection had been done and obtained 6.885 U/mL of laccase activity.
Keywords: 330; Adrenaline; Biosensor; Laccase; Solid state fermentation